Pemberdayaan Siswa dalam Pengolahan Sampah Organik menjadi Pupuk Kompos untuk Menanamkan Literasi Lingkungan - Riva Ismawati; Rina Rahayu (Jurnal Pengabdian KOLABORATIF, 2024)
Education needs to play a role in overcoming environmental problems by forming environmentally literate individuals. Environmentally literate individuals are individuals who are responsible for their behavior, respect the environment, and understand the problems that occur in the environment. Therefore, environmental literacy needs to be instilled and trained from an early age. It is known that students are not aware of various environmental problems, and efforts to preserve the environment, environmental education has not been integrated into classroom learning, and the absence of waste management practices in schools makes students' environmental literacy low. The methods used in PKM include (a) case studies and discussions, and (b) the practice of making compost and using it to fertilize plants. PKM activities begin with contracts and at the end of the activity, an evaluation is carried out to find out the achievements of PKM implementation. PKM activities were carried out in two partner schools namely SD Muhammadiyah 2 Alternative and SD Negeri Keramat 5 Magelang. Participants who are students from the two partner schools have understood environmental issues, and waste management as an effort to preserve the environment, and are skilled in processing organic waste into compost. Participants showed interest and enthusiasm during the PKM activities.